2020
DOI: 10.1002/tea.21671
|View full text |Cite
|
Sign up to set email alerts
|

“It's a lot of people in different places working on many ideas”: Possibilities from global history of science to Learning about nature of science

Abstract: This article describes a teaching experience at an year 8 classroom (students aged 12–13) in a state secondary school in London, UK that aimed at widening learning about nature of science (NOS) with the input from the field of Global History of Science (HOS), which looks at science as a product of material and cognitive exchanges, appropriations and collaborations. Teaching and learning plans (TLPs) informed by this historical framework were developed by the researcher and one science teacher to integrate NOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
(122 reference statements)
1
17
0
2
Order By: Relevance
“…First, among the potentialities of the proposed 'decolonial' approach to science curricula there was its affordances to the integration of both the products (content) and the processes and attitudes involved in scientific/technological developments (NOS), a well-known challenge in school science (Reiss, 2018), where views of it as a dichotomy between content and NOS still persist, with the latter usually seen as an 'add-on'. The historical-epistemological stance adopted in this study-an intercultural model of HOS that looks at knowledge and process as inherently linked-coupled with storyline/integrated strategies seem to have allowed for their more natural connection, without competing for space in the official curriculum, while also resulting in the participant students' exam marks being above school A's average that year (Gandolfi, 2020b). Future studies could further explore how these strategies may translate to different school systems and science curricula, including to year groups taking part in high-stake examinations, such as the GCSEs and A-levels in England.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, among the potentialities of the proposed 'decolonial' approach to science curricula there was its affordances to the integration of both the products (content) and the processes and attitudes involved in scientific/technological developments (NOS), a well-known challenge in school science (Reiss, 2018), where views of it as a dichotomy between content and NOS still persist, with the latter usually seen as an 'add-on'. The historical-epistemological stance adopted in this study-an intercultural model of HOS that looks at knowledge and process as inherently linked-coupled with storyline/integrated strategies seem to have allowed for their more natural connection, without competing for space in the official curriculum, while also resulting in the participant students' exam marks being above school A's average that year (Gandolfi, 2020b). Future studies could further explore how these strategies may translate to different school systems and science curricula, including to year groups taking part in high-stake examinations, such as the GCSEs and A-levels in England.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these perspectives have already been further explored elsewhere: specific reflections about the nature of this researcher-teacher partnership-for instance, around its impact on the teacher's professional growth and curricular agency, and my position as a research subject-can be found in Gandolfi (2020a). In turn, its implications for students' learning and engagement with school science have been analysed in Gandolfi (2020b). Here I will focus on another, but interrelated, angle of educational practice-the curriculum-exploring what a decolonial approach based on the intercultural model of HOS can look like in the context of the secondary school science in England, addressing the following questions: 'how can science teachers decolonise mainstream science curricula such as the National Curriculum in England with inputs from the STS field?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet the social, historical, and cultural contexts that surround East Asian science were felt more comfortable and meaningful to the PSTs. This resonates with Gandolfi's (2020b) argument that considering global history of science can promote learners' knowledge in social and cultural aspects of science. From a postcolonial view, experiences such as this can prompt critical reflection on the Eurocentric view of science created and perpetuated by the science curriculum and provide an opportunity to adapting science teaching to be culturally responsive (Medin and Bang 2014).…”
Section: Discussionmentioning
confidence: 54%
“…(Fan 2012, p. 251). Gandolfi's (2020b) study is an example of how global history of science can help to rethink the "science" in what we call the nature of science (NOS) and help to deepen NOS understanding. In one of the modules that she implemented with a secondary school teacher in England, they used a narrative that the compass was first invented in ancient China and then was spread to Europe through the Silk Road.…”
Section: Global History Of Sciencementioning
confidence: 99%